Multi-level governance for sustainability. Workshop of the thematic network - 5th research programme: Improvement of sustainability strategy elaboration for economic, environmental and social policy integration in Europe, Vienna 18 - 19 march 2004. Themenheft. - (:unkn) unknown (TU Wien, 2005)
Die Themen im Einzelnen: F.O. Wolf: Challenges of a multi-level governance for sustainability: What can the European experience teach us? (S. 1-2). M. Getzner: Regional sustainability and governance: The potentials of regional state aid (S. 3-7). K.N. Farrell: Different forms of difference in multi-level governance for sustainability: Connections between gender and complexity theory perspectives (S. 9-19). J.H. Spangenberg: Institutionelle Nachhaltigkeitsindikatoren - Der institutionelle Gehalt von Agenda 21 und die Ableitung zugehöriger Indikatoren (S. 21-38). R. Czeskleba-Dupont: Global Governance (S. 39-42). P. Paust-Lassen: Die Relevanz gesellschaftlicher Geschlechterverhältnisse für die Entwicklung einer europäischen Nachhaltigkeitsstrategie (S. 43-46). P.M. Weaver: Integrated sustainability assessment: Toward an new paradigm (S. 47-53). M. Spitzner: Netzgebundene Infrastrukturen unter Veränderungsdruck - Entwicklung eines Gender-Analyse-Konzepts zu Privatisierung, Liberalisierung und sozial-ökologischer Regulation (S. 55-78). difu
Keywords: Umweltschutz; Entwicklungsplanung; Planungspolitik; Leitbild; Indikator; Theorie; Methode; Regionalpolitik; Infrastruktur; Daseinsvorsorge; Privatisierung; Integrierte Planung; Interdisziplinarität; Nachhaltigkeit; Strategie; Agenda 21; Liberalisierung; Regulierung; Gender Mainstreaming